Unraveling the neurophysiology of muscle fatigue - Enoka, R. M.; Baudry, S.; Rudroff, T.; Farina, D.; Klass, M.; Duchateau, J. (Journal of Electromyography and Kinesiology, 2011)
Despite 100 years of research since the seminal work of Angelo Mosso (1846-1910), our understanding of the interactions between the nervous system and muscle during the performance of fatiguing contractions remains rather rudimentary. Although the nervous system simply needs to provide an activation signal that will elicit the net muscle torque required for a prescribed action, changes in the number and diversity of synaptic inputs that must be integrated by the spinal motor neurons to accommodate the changes in the force-producing capabilities of the muscle fibers complicate the process of generating the requisite activation signal. This brief review examines two ways in which the activation signal can be compromised during sustained contractions and thereby contribute to the rate at which the muscles fatigue. These examples provide insight on the types of adjustments that occur in the nervous system during fatiguing contractions, but emphasize that much remains to be learned about the physiological processes that contribute to the phenomenon known as muscle fatigue.